The Implementation of Dispersion Effect on Rise Time Budget and Power Link Budget on Optical Links at PT Telkom Akses Rungkut Surabaya Website Based - Rafidatus Sabrina; Abdul Rasyid; Yoyok Heru Prasetyo (Jurnal Jaringan Telekomunikasi, 2022)
Along with the development of an increasingly rapid era, it is directly proportional to the development of technology. Optical fiber is a transmission medium used in telecommunications. The quality of information transmissions through this cable transmission medium is influenced by a number of variables, including attenuation and dispersion. The rising time budget value is determined by the dispersion, and the power link budget is determined by measuring the attenuation that influences the light's path during data transmission and causes dispersion. The results showed that the chromatic dispersion value of the measurement results on this optical link was influenced by bending, the length of the distance on the path, the splicing of optical fibers, and due to the deployment of optical fibers. The system still performs at the required levels, i.e., at a power link budget of less than -15 dBm and a rise time budget of less than 70 ps, hence the optical link results have no impact on the system's performance. The results of the implementation of the website in this study display the results of measurements and calculations that were previously carried out where the results of these measurements and calculations can be seen in a table that has been integrated between databases to store data values ??with an online map which is then displayed the value on the map or online maps on the website containing data from the measurement results and parameter calculations on optical fiber owned by PT. Telkom Access.